Effect of phosphorus and bio-fertilizers in pigeonpea and its residual effect on the productivity of wheat under pigeonpea-wheat cropping system - Kumar, Sandeep; Tomar, Tejveer Singh; Tomar, Savita; Singh, Subey (Annals of Agricultural Research, 2016)
A two-year field experiment was conducted at Janta Vediv College Baraut, Baghpat, Uttar Pradesh during 2008-09 and 2009-10 on sandy clay soil to study the efficiency of phosphorus and bio-fertilizers applied in pigeonpea and its residual effect on succeeding wheat crop in pigeonpea-wheat cropping system. The residual N and P content in soil was higher after the harvest of pigeonpea crop than its initial contents in soil. The crop yield and uptake of N and P in pigeonpea was significantly increased with the increasing levels of phosphorus up to 60 kg P2O 5 /ha, whereas, decline in residual P content in soil after harvest of both crops was observed in 0 kg P2O5/ha and no inoculation treatments as compared to initial P content present in soil. On the other hand P content was found to increase with increasing levels of P applied in pigeonpea crop. Dual inoculation of Rhizobium + phosphorus solubilizing bacteria increased productivity of both the crops and available N and P contents in soil after pigeonpea harvest. However, in no inoculation of bio-fertilizers N content was significantly decreased in soil after wheat harvest. Phosphorus solubilizing bacteria inoculated treatments improved the available soil P status as compared to no inoculation treatment. N content in soil was found to decrease in soil after wheat harvest in all P levels and bio-fertilizers treatments, while P was increased in PSB inoculated treatments irrespective to phosphorus treatments. Â